ANALYSIS OF BUSINESS STRATEGY DECISION MAKING IN INCREASING SALES OF WAROENG STEAK AND SHAKE BANDAR LAMPUNG - Oktaviannur, M.; Redaputri, Appin Purisky; Ayunara, Meyta; Dunan, Hendri; Jayasinga, Heylin Idelia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The high competition in the steak restaurant business in the city of Bandar Lampung has an impact on the management of Waroeng Steak and Shake so that the income received fluctuates every month, this makes researchers aim to find out what alternative strategies are appropriate for Waroeng Steak and Shake and which strategies are become a priority for Waroeng Steak and Shake, Gatot Subroto Bandar Lampung Branch. This researcher uses descriptive analysis method and uses the Soft System Methodology (SSM) method and the Annalitical hierarchy Process (AHP) method. The results of this study indicate that there are five sub-criteria internal factors and external factors there are three sub-criteria. The results of the decision making model using AHP show that Goal in Waroeng Steak and Shake increases sales with the first priority strategy by creating more modern service changes in, developing new types of food, promoting via billboards and promoting word of mouth.modern in, developing types of food new, promotions via billboards and word of mouth promotions. Keywords: Business Strategy, Analytical Hierarchy Process (AHP), Decision Making